Pseudomembranous tracheobronchial aspergillosis: a rare manifestation of invasive aspergillosis in a non-neutropenic patient with Hodgkin's disease = Pseudomembranöse tracheobronchiale aspergillose - Buchheidt, Dieter; Weiss, A.; Reiter, Sebastian; Hartung, G.; Hehlmann, Rüdiger (Mycoses, 2003)
Pseudomembranous tracheobronchial aspergillosis coincident with systemic pulmonary aspergillosis represents a rare manifestation of fungal infection in immunocompromized hosts. We report on a patient with recurrent Hodgkin's disease, showing this infectious pattern after treatment with corticosteroids within the antineoplastic schedule, whereas neutropenia - the main risk factor for mold infections - had not occurred. An impaired number of helper T lymphocytes was merely detected as an additional, but hypothetical risk factor, when investigating the status of immunosuppression. Treated systemically with amphotericin B, the patient recovered quickly, although reported mortality rates are disastrous. What is crucial for the clinical management is an early diagnosis by bronchoscopy and cultural proof of the pathogen followed by an adequate antifungal treatment.
Gesehen am 16.05.2022